Rare Earth and Other Geochemical Studies of Archean Banded Iron Formation: Sherman and Adams Mines, Ontario - Bowins, Robert J. (My University, 1989)
Banded iron-formation (BIF), an iron-rich chemical sediment of Precambrian age, from the Sherman Mine at Temagami and the Adams Mine at Kirkland Lake, Ontario, were the subject of a detailed geochemical study. The rare earth elements were extensively studied with lesser emphasis on sulphur isotope, trace element and major element compositions. Procedures were developed to quantitatively estimate the relative chemical and clastic components of mixed sediment lithologies and to correct both volcanic and volcaniclastic major element analyses for alteration resulting from weathering or metamorphism.
Analyses of the rare earth patterns suggest inputs from diverse sources; from clays resulting from submarine weathering, from direct addition of fine grained volcaniclastic detritus, from ambient seawater and from submarine hydrothermal vents. In addition, the concave-down curvature of the light rare earths of some samples suggests a mineral control such as marine apatite. Also, the positively anomalous values of La suggest a component whose REE contents were controlled by the solubility product of sparingly soluble solids as opposed to the ion speciation and exchange equilibria which control the rare earth contents of normal marine waters. Combinations of rare earths from these sources allowed synthesis of all patterns measured, frequently to a precision of 5% or better.
Analyses of sulphur isotopes of pyrite found in the iron formation showed greater variability in volcanic as opposed to clastic sediment host lithologies. Sulphide-facies iron formation had an isotopic signature indistinguishable from volcanic sulphides and it was not possible to unambiguously infer the presence of biological activity.
Anomalies in the distribution of tungsten in BIF were interpreted to be the result of either syngenetic or epigenetic processes. BIF may become enriched in tungsten as a result of either its tendency to deform by brittle fracture or because of primary volcanic exhalative addition.
The data suggest that Archean basinal water were enriched in Fe, Si, Eu, Mn and P compared to modern counterparts. The absolute abundances of the REE and trace elements in the iron-formations studied were low compared to previously published values.
Higher statistical variability in both the sulphur isotope data and REE from BIF hosted in volcanic as compared with detrital rocks, and a persistent large positive Eu anomaly, all suggest inputs of hydrothermal fluids to the depositional basin. However, the lack of internal correlation of the volcanogenic elements suggests depositional sites were not necessarily proximal to source vents. This results in a decoupling of source from sink in the case of iron formation deposition in Archean marine basins having very low oxygen content. Any correlation of BIF with massive sulphide or other exhalitive type mineralization would be on a basinal rather than a deposit scale.
Keywords: Geology; Geology